Analysis for Science Librarians of the 2015 Nobel Prize in Chemistry: DNA Repair Mechanisms. Issue 1 (2nd January 2016) - Wrublewski, Donna T.
ABSTRACT: The 2015 Nobel Prize in Chemistry recognized three scientists for their contributions to understanding the mechanisms of DNA repair. Tomas Lindahl discovered the mechanism—base excision repair—by which individual bases, damaged by degradation, for example, are repaired. Paul Modrich showed how DNA repairs mismatched bases that occur during DNA replication. Aziz Sancar elucidated the complete mechanism for nucleotide excision repair, the process by which DNA damaged by UV irradiation or other mutagenic agents is fixed. Without these mechanisms, life as we know it would not exist due to the number of errors and mutations that appear in DNA.